Física de Partículas y el Origen de la Masa - Vaquera Araujo, Carlos Alberto; Napsuciale Mendivil, Mauro (Acta Universitaria, 2009)
A brief introduction is given to the problem of the origin of mass from the perspective of modern particle physics. Also an elementary discussion about the standard model of particles and their interactions is presented, together with a sketch of the Higgs mechanism, which in this model is responsible for the generation of the masses of the fundamental particles.